Oilseeds scenario in Himachal Pradesh: analysis and some reflections: OILSEEDS SCENARIO IN HIMACHAL PRADESH: ANALYSIS AND SOME REFLECTIONS - VIRENDER KUMAR; SHIVALI MASAND (Journal of Oilseeds Research, 2020)
Oilseeds are very important due to being an integral part of Indian kitchen and imports basket. The diverse agro-ecological conditions in India favour growing ofmanyoilseeds, whose demand goes unmet domestically. Area, production and yield of oilseeds in India have witnessed positive growth over time. But these appear to be missing crops in Himachal Pradesh. Sesamum in kharif and rapeseed & mustard in rabi are the most important crops. The present study analysed the trends in area, production and yields ofthese two oilseed crops in Himachal Pradesh using time-series data for the period 1974-75 to 2016-17. The economics of cultivating these two crops was also studied to examine their profitability. The results revealed negative and significant growth rate for area under all oilseeds in the state, while the same for the yield was positive and significant. The growth in production of rapeseed & mustard was contributed both by acreage as well as yield during the study period. The area under sesamum observed a steep fall in the state, more so during the past two and a half decades. Human labour alone accounted for the highest cost in these crops on sample farms. The cost and returns analysis clearly brought out that the two oilseed crops were profitable only when paid out cost were considered. Also, sesamum turned out to be more profitable as compared to rapeseed & mustard due to higher output price. These results call for incentivized approach to re-popularize these crucial crops in the state through an appropriate mix of technology and extension services.